2007
DOI: 10.1002/cyto.a.20471
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐microarray analysis of antigen‐specific B‐cells: Single cell analysis of antigen receptor expression and specificity

Abstract: The authors previously developed a cell-microarray system that effectively detects antigen-specific B-cells by monitoring intracellular Ca 21 at single cell levels. Here they present a novel method to detect antigen-specific B-cells using cell-microarray system. To detect antigen-specific B-cells, they arrayed live lymphocytes on a chip, stained cells with fluorescence-labeled nonspecific proteins, and analyzed them with a fluorescence scanner to detect nonspecific protein binding to B-cells. They then stained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…Compared with that protocol, the protocol in this study showed much higher detection efficiency because we could amplify HyHEL10 cDNA from 95% and 67% of retrieved cells out of 0.05% and 0.01% of the MD4 B cells, respectively. We also reported that we could amplify HyHEL10 cDNA from 50% of the retrieved cells when analyzing the 0.01% MD4 B-cell preparation by detecting the binding of the fluorescence-labeled antigen (17). In that protocol, it took about 1 h to detect antigen-specific B cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Compared with that protocol, the protocol in this study showed much higher detection efficiency because we could amplify HyHEL10 cDNA from 95% and 67% of retrieved cells out of 0.05% and 0.01% of the MD4 B cells, respectively. We also reported that we could amplify HyHEL10 cDNA from 50% of the retrieved cells when analyzing the 0.01% MD4 B-cell preparation by detecting the binding of the fluorescence-labeled antigen (17). In that protocol, it took about 1 h to detect antigen-specific B cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cytomics is becoming increasingly important for analyzing cell conditions and cellular responses to stimuli from extracellular milieu, which will contribute to drug discovery as well as predictive medicine. Cell microarray-based analysis offers one way for analyzing cytomics; it has been conventionally performed with a single parameter (11)(12)(13)(14)(15)(16)(17)(18). Here, for the first time, we present a method of two-parameter cell microarray-based time-lapse analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations